Adsorption geometry and electronic structure of a charge-transfer-complex: TTF-PYZ2 on Ag(110). (18th January 2021) - Kretz, Patrick; Waltar, Kay; Geng, Yan; Metzger, Christian; Graus, Martin; Schöll, Achim; Reinert, Friedrich; Liu, Shi-Xia; Decurtins, Silvio; Hengsberger, Matthias; Osterwalder, Jürg; Castiglioni, Luca
Abstract: We study electronic properties and adsorption geometries of the molecular charge-transfer-complex tetrathiafulvalene-dipyrazine on Ag(110). Using a combination of angle-resolved photoemission and electron diffraction, supported by DFT-based simulations, renders a comprehensive picture of this interesting system. We find low interaction between the substrate and the molecule and thus little changes of the molecular geometry upon adsorption, as compared to the free gas phase molecule. Five electronic valence states can be unambiguously assigned owing to their distinctive photoemission patterns. The molecules adsorb aligned with the Ag rows in the first layer, while they are slightly rotated in the second layer. Additional intensity of the molecular photoemission signal near the Fermi energy indicates partial charge-transfer into formerly unoccupied states, most likely of intermolecular origin.